Design and characterization of Kerberos: a 48-channel analog pulse processing and data acquisition platform. (12th July 2021) - King, P.; Gugiatti, M.; Carminati, M.; Buonanno, L.; Borghi, G.; Pepponi, G.; Lechner, P.; Siegmann, D.; Urban, K.; Houdy, T.; Mertens, S.; Fiorini, C.
Abstract: A multi-channel data processing and acquisition system based on an analog ASIC (SFERA) has been designed and realized. The platform, called Kerberos, is suitable for the readout of large arrays of Silicon Drift Detector (SDD) for X-ray, γ-ray and electron spectroscopy applications. Each one of its 48 inputs is equipped with a 9 th order semi-Gaussian shaping amplifier with programmable peaking time (0.5, 1, 2, 3, 4 and 6 ). The pulse amplitudes are multiplexed into three 16-bit high linearity SAR ADCs and digitized into an Artix-7 FPGA module. Kerberos will be used for the characterization of monolithic SDD matrices for the TRISTAN project. Many different readout strategies can be selected on Kerberos Graphic User Interface: for TRISTAN it has been decided to use a full detector readout strategy, with maximum input throughput of about 166 kcount/s. This work presents a full characterization of this scalable platform and its use with several detectors types (SDD, micro-strips) in X-ray, gamma and beta spectroscopy.